Proposta de indicadores de sustentabilidade para o projeto de pontes de pequenos vãos - Milani, Cleovir José (2020)
The subject of this work is the construction of bridges, infrastructure constructions essential to the transportation of people and goods, referring to the concern in the rationalization of designs and processes of bridge construction, focusing on reducing costs, consumption of resources and environmental impacts. The objective was to apply sustainability assessment techniques in the life cycle of small span bridge superstructures, proposing environmental and economic indicators to be integrated in the decision making process, aiming to mitigate the environmental impact, reduce the consumption of resources and minimize the costs in their life cycle. The study analyzed 405 small span bridges, starting at 6 meters up to 20 meters, of the following types: steel and concrete composite bridges; reinforced concrete bridges cast in loco; precast reinforced and prestressed concrete bridges, quantifying environmental impacts and costs through the Life Cycle Environmental Assessment and Life Cycle Cost Assessment, for the proposition of sustainability indicators for the construction of bridges, following the frontier of systems for the extraction of materials until the end of life (from the cradle to the grave). The guidelines of national and international standards were used, based on the Ecoinvent 3.5 database of 2018, the global reach method ReCiPe 2016 V1.1, and the SimaPro software version 9.0.0.32. In the results, it was observed the indication of the steel and concrete composite bridge with two P1 M(S) 2V steel beams as the one that causes less impact on the environment; the bridge superstructure of the steel and concrete composite model with P4 M(L) 2V rolled steel beams is the bridge that presents the lowest cost per m² for the lengths of 6m and 7m; the reinforced precast concrete model, P23 PMD 5V, is the most economical in the spans of 8m to 20m. In conclusion, it was observed that steel and concrete composite type P1 M(S) 2 V bridges and precast type P23 PMD 5V bridges can be indicated as the most efficient from the sustainability point of view.